2010
DOI: 10.1042/bc20100034
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing protein interactions involved in the formation of the 42S RNP storage particle of Xenopus oocytes

Abstract: Background information. During early phases of Xenopus oogenesis, 5S rRNA and tRNAs are stored in the cytoplasm of young oocytes in the form of a common RNA-protein complex termed the 42S particle. These storage particles comprise two kinds of proteins with different RNA binding specificities. The tRNA-binding protein 42Sp50 belongs to the EF1A (eukaryotic translation elongation factor 1A) family of translation elongation factors, while 42Sp43 is a diverged form of the transcription factor TFIIIA (transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…3b, 11 counts with highest rich factor in Table S6). Thus, ribosome biogenesis was higher in normal and gsdf null ovaries, but lower in normal testes, which is consistent with the quantity of ribosomes being actively transcribed and accumulated during early oogenesis (25,26). In contrast, pathways of microtubule-based phagosomes and gap junctions, as well as cell cycle, represented by pcna (proliferating cell nuclear antigen), were enriched in B but was downregulated in C and A, reflecting that these proteins are higher in normal testes than in normal ovaries or gsdf-deficient ovaries.…”
Section: Diversity Of Germ Responding To Gsdfsupporting
confidence: 77%
See 1 more Smart Citation
“…3b, 11 counts with highest rich factor in Table S6). Thus, ribosome biogenesis was higher in normal and gsdf null ovaries, but lower in normal testes, which is consistent with the quantity of ribosomes being actively transcribed and accumulated during early oogenesis (25,26). In contrast, pathways of microtubule-based phagosomes and gap junctions, as well as cell cycle, represented by pcna (proliferating cell nuclear antigen), were enriched in B but was downregulated in C and A, reflecting that these proteins are higher in normal testes than in normal ovaries or gsdf-deficient ovaries.…”
Section: Diversity Of Germ Responding To Gsdfsupporting
confidence: 77%
“…It was reported that loss of dlc1 in the cyst cells caused gonial cell hyperplasia in Drosophila testes (29), resembling the phenotypes of germ cell overproliferation in gsdf-depletion or amhr2-mutation testes (8,10,18). In addition to ribosomal proteins, eukaryotic translation initiation factor 3 (eIF3) subunits, the structural maintenance of chromosomes 5 (SMC5), elongation factor (eEF1 ), and its ovarian isoform (42Sp50), which are expressed in frog and medaka oocytes (25,26), were found among the 36 identified peptides.…”
Section: Capture Of Gsdf-binding Protein By His-tagged Rgsdf Pull-dowmentioning
confidence: 99%
“…P43 5S RNA-binding protein is combined with 5S rRNA to comprise 42S ribonucleoprotein storage particle. In addition, transcription factor IIIA acts as both a positive transcription factor for 5S RNA genes and a specific RNA-binding protein that complex with 5S RNA in oocytes to form the 7S ribonucleoprotein storage particle [48]. According to Diaz De Cerio et al, 5 S RNA and associate protein could constitute a sensitive and universal marker of oogenesis and oocyte differentiation in fish [49].…”
Section: Discussionmentioning
confidence: 99%
“…Under special circumstances, cells transcribe 5S rRNA in excess and accumulate it in the cytoplasm in storage particles for subsequent mobilization to the nucleolus. This event has been studied in detail in Xenopus laevis oocytes [9], where 5S rRNA associates with p43, a 43 kDa protein diverged from TFIIIA.…”
Section: Introductionmentioning
confidence: 99%